2012
DOI: 10.5897/ajmr-11-1300
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the insecticidal activity of Fusarium solani and Trichoderma harzianum against cockroaches; Periplaneta Americana

Abstract: Microbial control is one possible option to reduce cockroaches' populations. On searching for microbial control of cockroaches, a laboratory study was carried out to investigate the effect of spore suspension and metabolites of both fungi Trichoderma harzianum and Fusarium solani against cockroaches; Periplaneta americana. In this study we determined the pathogenicity of both spore suspension and metabolites of both fungi. Spore suspension was applied to the roaches either as a food additive or as a spray. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The survival rate decreased by increasing the concentration during exposure periods. These results in agreement with the results of Abdul-Wahid et al [21] who reported that reduction of cockroaches' (Periplaneta americana) population due to fungal treatment by T. harzianum was 100% at 24 h. Sakran [22] proved that Butachlor and fluazifop-p-butyl (herbicides) caused reduction in the survival rate of Biomphalaria alexandrina. Al-Assiuty et al [23], show that the abundance and species diversity of oribatid mites varies greatly by the effect of fungicides (T. harzianum and Pythium oligandrum) by their taxon and fungicide.…”
Section: Tolerance Effect Of Different Concentrations Of T Harzianumsupporting
confidence: 90%
See 1 more Smart Citation
“…The survival rate decreased by increasing the concentration during exposure periods. These results in agreement with the results of Abdul-Wahid et al [21] who reported that reduction of cockroaches' (Periplaneta americana) population due to fungal treatment by T. harzianum was 100% at 24 h. Sakran [22] proved that Butachlor and fluazifop-p-butyl (herbicides) caused reduction in the survival rate of Biomphalaria alexandrina. Al-Assiuty et al [23], show that the abundance and species diversity of oribatid mites varies greatly by the effect of fungicides (T. harzianum and Pythium oligandrum) by their taxon and fungicide.…”
Section: Tolerance Effect Of Different Concentrations Of T Harzianumsupporting
confidence: 90%
“…It was toxic to the shrimp (Palaemonetes pugio) when LC 50 was 52 mg/l [29]. Another cause of mortality can be attributed to the blockage of fungi spores to the gills of P. clarkii, as what happened to the cockroaches; Periplaneta americana by Abdul-Wahid et al [21].…”
Section: Tolerance Effect Of Different Concentrations Of T Harzianummentioning
confidence: 99%
“…In contrast to the effects of fungal conidia (Lopes et al 2011; Sabry et al 2011; Khalid et al 2012; Nussenbaum et al 2012), researchers have paid more attention to the role of fungal secondary metabolites on host insects in recent years (Sokolova et al 1999; Xia et al 2000; Xia et al 2001; Zibaee et al 2009a; Zibaee et al 2011). Abdul-Wahid et al (2012) reported the pathogenicity of both a spore suspension and metabolite solution of two fungi, Trichoderma harzianum and Fusarium solani , against cockroaches ( Periplaneta americana ). Our study showed that B. brongniartii and its metabolites had toxic effects on the pine caterpillar D. tabulaeformis larvae, which is in agreement with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the effects of fungal conidia (Lopes et al 2011;Sabry et al 2011;Khalid et al 2012;Nussenbaum et al 2012), researchers have paid more attention to the role of fungal secondary metabolites on host insects in recent years (Sokolova et al 1999;Xia et al 2000;Xia et al 2001;Zibaee et al 2009a;Zibaee et al 2011). Abdul-Wahid et al (2012) reported the pathogenicity of both a spore suspension and metabolite solution of two fungi, Trichoderma harzianum and Fusarium solani, against cockroaches (Periplaneta americana). Our study showed that B. brongniartii and its metabolites had toxic effects on the pine caterpillar D. tabulaeformis larvae, which is in agreement with previous studies.…”
Section: Discussionmentioning
confidence: 99%